2021
DOI: 10.1002/bbb.2264
|View full text |Cite
|
Sign up to set email alerts
|

Waste sugarcane bagasse‐derived nanocatalyst for microwave‐assisted transesterification: Thermal, kinetic and optimization study

Abstract: The production of biodiesel has increased globally during the last decade to overcome the problems of increasing prices of petro-diesel and the depletion of fossil fuels. The present study aimed to utilize agro-waste sugarcane bagasse (SCB) to synthesize a heterogeneous acid catalyst for biodiesel production using waste cooking oil. Waste sugarcane bagasse was converted into biochar through partial carbonization and activated via sulfonation by using acid solutions of different concentration i.e., 1M, 3M, 5M a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Furthermore, an excess of methanol may not result in improved catalytic efficiency since a considerable quantity of alcohol might limit oleic acid accessibility to the active sites of the catalyst. Therefore, a desired molar ratio of methanol is required for the esterification to carry out the reaction in a forward direction 27 , 30 . The impact of oleic acid to methanol molar ratio on conversion yield was investigated by changing the molar ratio to 1:12, 1:16, 1:20, and 1:24, at 85 °C for 60 min and 9 wt% catalyst doses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an excess of methanol may not result in improved catalytic efficiency since a considerable quantity of alcohol might limit oleic acid accessibility to the active sites of the catalyst. Therefore, a desired molar ratio of methanol is required for the esterification to carry out the reaction in a forward direction 27 , 30 . The impact of oleic acid to methanol molar ratio on conversion yield was investigated by changing the molar ratio to 1:12, 1:16, 1:20, and 1:24, at 85 °C for 60 min and 9 wt% catalyst doses.…”
Section: Resultsmentioning
confidence: 99%
“…SFHCs derived from biomass have numerous specific characteristics, such as providing excellent conversion efficiency, being easily separable from the reaction mixture, and being highly reusable, cost-effective, and environmentally friendly. Numerous SFHCs, including, Areca nut husk 24 , Acai stone 25 , citrus limetta peel 26 , Sugarcane bagasse 27 , and Sargassum horneri 28 , Pineapple leaves 29 , Date pits 30 , Tucuma peels 31 have been reported for biodiesel production. However, these existing catalysts have several problems, and they provide lower ester content in biodiesel with harsh reaction conditions, which affect the cost of biodiesel production.…”
Section: Introductionmentioning
confidence: 99%
“…The Experimental Testing was also been conducted on the physical properties of the developed composite samples. 13,14…”
Section: Methodsmentioning
confidence: 99%
“…The Experimental Testing was also been conducted on the physical properties of the developed composite samples. 13,14 Experimental testing methods Measurement of sound absorption coefficient. The impedance tube method is mainly applied to measure the sound absorption coefficient (SAC) of composite materials.…”
Section: Development Of Composite Materialsmentioning
confidence: 99%
“…Nazir et al [123] reported the conversion of waste cooking oil into biodiesel using sugarcane bagasse biochar as a catalyst. Microwave irradiation was used to maintain the reaction temperature at 60 • C. The highest biodiesel yield of 92.12% was obtained within 15 min using 5 wt.% of catalyst loading at a 1:15 oil-to-methanol molar ratio.…”
Section: Microwave-assisted Transesterification For Biodiesel Productionmentioning
confidence: 99%